2006
DOI: 10.1108/09534810610643695
|View full text |Cite
|
Sign up to set email alerts
|

A structurationist analysis of post‐bureaucracy in modernity and late modernity

Abstract: PurposeThe purpose of this paper is to use case study evidence to show that post‐bureaucracy is less marked by a discontinuity in surveillance than by its displacement and intensification.Design/methodology/approachThe paper describes the complex changes that occurred at the International Development Research Center, a Canadian public corporation.FindingsFundamental clash of values is evident. The reform has brought about a “new order” which relies on a centralized model of governance. Moves towards the “post‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Besides, project management is not simply a toolbox, and the concerns it raises call for different frameworks to explore it (Sydow et al, 2004). The project-based organisational form and project management appear suitable for managing flexibility/work distribution issues but the control/work organisation matters they involve require critical research (Hodgson, 2002;Briand and Bellemare, 2006). On the whole, empirical studies dealing with management control over knowledge workers in project-based settings have shown that management control has in fact been re-invented (Clegg and Courpasson, 2004;Hodgson, 2004;Éminet, 2006) and even strengthened (Briand and Bellemare, 2006).…”
Section: Research Issue and Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, project management is not simply a toolbox, and the concerns it raises call for different frameworks to explore it (Sydow et al, 2004). The project-based organisational form and project management appear suitable for managing flexibility/work distribution issues but the control/work organisation matters they involve require critical research (Hodgson, 2002;Briand and Bellemare, 2006). On the whole, empirical studies dealing with management control over knowledge workers in project-based settings have shown that management control has in fact been re-invented (Clegg and Courpasson, 2004;Hodgson, 2004;Éminet, 2006) and even strengthened (Briand and Bellemare, 2006).…”
Section: Research Issue and Contextmentioning
confidence: 99%
“…The project-based organisational form and project management appear suitable for managing flexibility/work distribution issues but the control/work organisation matters they involve require critical research (Hodgson, 2002;Briand and Bellemare, 2006). On the whole, empirical studies dealing with management control over knowledge workers in project-based settings have shown that management control has in fact been re-invented (Clegg and Courpasson, 2004;Hodgson, 2004;Éminet, 2006) and even strengthened (Briand and Bellemare, 2006). Similar conclusions have been reached in studies dealing with teamwork and 'post-bureaucratic' structures (Gallie et al, 2012;Johnson et al, 2009;Bolin and Härenstam, 2008).…”
Section: Research Issue and Contextmentioning
confidence: 99%
“…Following Giddens' work, a structurationist definition of organizations frequently used by organization theorists invites us to reframe organizations as administrative systems [47]. Administrative systems are characterized by systemic relations in time and space "coordinated and controlled through the exercise of administrative procedures which ultimately are meant to serve the intentions of the superordinate agents" [44].…”
Section: Proposition 1: Knowledge Is a Power Resource Pivotal To The mentioning
confidence: 99%
“…However, despite significant changes in organizational structures and practices, particularly since the 1970s, Weber's bureaucracy model is still a relevant and valuable analytical tool. For example, although the hierarchical structure may have been adapted, control is achieved, although in different ways (Bagguley, 1991;Briand & Bellemare, 2006;Courpasson, 2000;Heckscher, 1994;Kärreman & Alvesson, 2004;Procter, 2005;Walton, 2005, p. 588). Therefore, although organizations today may be structured differently than in Weber's time, they do not operate according to a radically new "organizing rationality or logic" (Courpasson & Reed, 2004, p. 7).…”
Section: Notesmentioning
confidence: 99%